The demography of COVID-19 deaths database, a gateway to well-documented international data - Arianna Caporali; Jenny Garcia; Étienne Couppié; Svitlana Poniakina; Magali Barbieri; Florian Bonnet; Carlo Giovanni Camarda; Emmanuelle Cambois; Iris Hourani; Daria Korotkova; France Meslé; Olga Penina; et al. (Scientific Data, 2022)
Measurement(s) mortality Technology Type(s) digital curation Factor Type(s) Death counts Sample Characteristic - Organism Homo sapiens • Covid-19 deaths Sample Characteristic - Environment Country Sample Characteristic - Location Austria, Belgium, Canada, England and Wales, Denmark, France, Germany, Italy, Japan, the Netherlands, Norway, Portugal, the Republic of Korea, the Republic of Moldova, Romania, Scotland, Spain, Sweden, Switzerland, Ukraine, and the United States of America